85.0k views
24 votes
Solve the equation, justify each step with an algebraic property. -11 = -12+ 2x +3

2 Answers

1 vote

Answer:


x = -1

Explanation:

Given the equation
-11 = -12 + 2x + 3 find
x

For resolve this you have to do basic algebraic operations in both sides of the equation, as follow:

First substract -3 in both sides of the equation


-14 = -12 + 2x

Later sum 12 in both sides of the equation


-2 = 2x

The final step is multiply by
(1)/(2) each side of the equation


-1 = x

So the final answer is
x = -1

User Karthikeyan Vedi
by
5.2k points
8 votes

Answer:

-1

Explanation:

Given the equation :

-11 = - 12 + 2x + 3

Collect like terms

-11 + 12 - 3 = 2x

-2 = 2x

-2 /2 = 2x/2

x = - 1

User Sonny D
by
6.0k points